Mitochondria-rich cells in Antarctic fish gills. - MASINI, MARIA ANGELA; M. STURLA; P. PRATO; B. UVA (Polar Biology, 2000)
We used transmission and scanning electron microscopy and an antibody to the inner mitochondrial membrane to study the presence and localisation of mitochondria-rich cells in the gills of two Antarctic ®shes, Chionodraco hamatus (Channichthyidae) and Trematomus bernacchii (Nototheniidae). The general morphology of the gills in the two species was slightly dierent: in T. bernacchii the ®lament and secondary lamellae were short and thicker, and mitochondria-rich cells were less numerous than in C. hamatus. In the two species the mitochondria-rich cells, distributed in the secondary and primary epithelium, were of the same morphological type, similar to the —-chloride cells of temperate seawater teleosts. The study was carried out to compare the mitochondria-rich cells of Antarctic ®shes to the chloride cells of temperate marine teleosts. Immunolocalisation, using a speci®c antibody to the —-subunit of Na+/K+-ATPase, was observed in nu- merous epithelial cells in the interlamellar epithelium and on the secondary lamellae, suggesting an active sodium chloride secretion.